Change of plans: an evaluation of the effectiveness and underlying mechanisms of successful talent transfer - Collins, R.; Collins, D.; MacNamara, A.; Jones, M. I. (Journal of Sports Sciences, 2014)
Talent transfer (TT) is a recently formalised process used to identify and develop talented athletes by selecting individuals who have already succeeded in one sport and transferring them to another. Despite the increasing popularity of TT amongst national organisations and sport governing body professionals, however, there is little empirical evidence as to its efficacy or how it may be most efficiently employed. Accordingly, this investigation was designed to gain a deeper understanding of the effectiveness and underlying mechanisms of TT, achieved through a two-part study. Stage 1 provided a quantitative analysis of the incidence and distribution or, in this respect, epidemiology of TT, finding the most popular transfer to be sprinting to bobsleigh, with an average transfer age of 19 years. Stage 2 scrutinised the TT process and explored the specific cases revealed in stage 1 by examining the perceptions of four sport science support specialists who had worked in TT settings, finding several emergent themes which, they felt, could explain the TT processes. The most prominent theme was the psychosocial mechanism of TT, an aspect currently missing from TT initiatives, suggesting that current TT systems are poorly structured and should redress their approach to develop a more integrated scheme that encompasses all potential mechanisms of transfer.